Exploring science fiction films in the post-human landscape: from ‘Ghost in the Shell’ to ‘Alita: Battle Angel’ / Luo Mu Ying ... [et al.] - Luo, Mu Ying; Ibrahim, Zainuddin; Lan, Mo; Qiu, Yu Ming (College of Creative Arts, 2024)
This paper examines the portrayal of post-human themes in Hollywood adaptations, particularly in "Alita: Battle Angel" and "Ghost in the Shell." Analyzing these films through the lens of post-human film theory, the study explores their exploration of human-machine fusion, identity, memory, and the ethical dimensions of technology. It highlights the similarities and differences in their approaches to these themes, including societal structures, individual autonomy, and techno-ethical challenges. The paper also discusses the impact of environmental and technological philosophical themes and links them to the theoretical viewpoints of Rachel Carson and Pete Townshend. By weaving these themes into a sci-fi narrative, these films contribute to a deeper understanding of the complex relationship between human evolution, technological advancement, and environmental considerations in the post-human era.